KOMITMEN PROFESIONAL SEBAGAI VARIABEL MODERASI PENGARUH INDEPENDENSI, KOMPETENSI DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT KAP DI YOGYAKARTA TAHUN 2015 - Handy Sudibyo (AKT 16 UMY 293, 2016)
The profession of public accountant (editor) is like a "sword", the auditor should consider the credibility and professional ethics, and on the other hand they also should face any pressures from the clients in various decision-making. If the editor is not able to resist any kinds of pressures from clients such as personal pressure, ethics and emotional even the financial, so it will affect to reducing its independency and impact to the auditing quality. Auditors should be able to provide the facts on the financial statements that there is no manipulation or misuse so that the auditor can give accurate decisions. One of the benefits of public accounting services is to provide accurate information. Financial statements audited by a public accountant more trustworthy and more accepted than the financial statements that not be audited. This research has goals in order to analyzing and providing the empirical evidence of professional commitment, competence, ethics, auditor independence and audit quality. The samples are 40 respondents who are 40 auditors who found in 6 KAP in Yogyakarta. As for answering the hypothesis in this research, it will use the multiple regression analysis with absolute difference, where have done with the classical assumption test. Based on the results of this research, concluded that this research is analyzing the professional commitment which impacts to the audit quality. So the depth and breadth of knowledge of an auditor as well as the more experienced in the field of auditing is also the peer review of the co-auditor, it shows the better quality of auditing. Keywords: Professional Commitment, Independence auditor, Competence Auditor, Ethics Auditor, and Audit Quality